Association of cytokine profile with prior treatment failure and revision surgery in chronic rhinosinusitis. Issue 1 (23rd June 2022) - Longino, Elizabeth S.; Labby, Alex B.; Wu, Jeffanie; Chapurin, Nikita; Li, Ping; Chandra, Rakesh K.; Turner, Justin H.; Chowdhury, Naweed I.
Abstract: Background: Inflammatory patterns in chronic rhinosinusitis (CRS) may predict disease severity, need for multiple sinus surgeries, and treatment response. This study analyzes nasal mucus inflammatory cytokine patterns in patients with (CRSwNP) and without (CRSsNP) nasal polyposis and their association with revision sinus surgery. Methods: A total of 319 CRS patients who underwent sinus surgery were included. Cytokines were quantified in intraoperative mucus specimens using a multiplex flow cytometric bead assay. Cytokine expression patterns in patients with 0, 1, and ≥2 previous surgeries were analyzed using Kruskal‐Wallis and principal component (PC) regression analyses. Results: There were 122 (38%) patients with CRSsNP and 197 (62%) with CRSwNP. On univariate analysis, interleukin (IL)‐1β, IL‐6, IL‐8, and IL‐21 were associated with increasing number of sinus surgeries in CRSsNP, as were IL‐2, IL‐4, IL‐5, IL‐6, IL‐9, IL‐17A, and tumor necrosis factor (TNF)‐α in CRSwNP. PC analysis with continuous Poisson regression in CRSwNP demonstrated that high IL‐5 and IL‐13 and low IL‐1β, IL‐12, and IL‐21 were associated with more prior surgeries. In CRSsNP low IL‐13 and high IL‐5 and regulated‐on‐activation, normal T‐cell–expressed and secreted (RANTES) were associated with more prior surgeries. Age remained a significant covariate in the full regression model for CRSsNP, but was nonsignificant in CRSwNP. Conclusion: In CRSwNP, elevated IL‐5 and IL‐13 levels were higher at time of surgery in patients with more prior surgeries. Type 2 cytokines in CRSsNP demonstrated mixed associations with revision surgery. For both phenotypes, IL‐10, IL‐12, and IL‐21 were consistently lower as number of prior surgeries increased, suggesting that treatment‐resistant disease may be modulated by impairment in these signaling pathways.